FIKIH KALENDER HIJRIAH UNIFIKATIF - Tasnim Rahman Fitra (istinbath, 2018)
Abstract: The idea of ??a Hijri’s unification calendar emerges in response to the lack of uniformity of the Hijri concept of calendar which affects the difference of beginning of the month, especially with regard to worship. Therefore, it needs an in-depth study of the Unificative Hijriah Calendar from the point of view of jurisprudence (fikih), namely the study of the use of reckoning (hisab), the understanding of matlak and the beginning of the day which are all dominated by differences in the understanding of the sharia foundation in al-Qur`an and Hadith. The method used is an inventory of related fiqh concepts, then conduct an in-depth analysis and conclude from the results of the analysis. As a result, the determination of the beginning of the month in worship should refer to the revelation or hadith of the Prophet Muhammad SAW that the Islamic concept of starting a new moon is due to the existence of a new moon (hilal). The solution for unification in worship should be left to the authority of each Muslim country. As for non-worship can be applied, but to minimize the problem, unification of this calendar must be started first in the local context. Abstrak: Pemikiran mengenai kalender Hijriah unifikatif muncul sebagai respons atas ketidakseragaman konsep kalender Hijriah umat Islam yang berdampak pada perbedaan memulai awal bulan, khususnya berkaitan dengan ibadah. Oleh sebab itu, perlu adanya kajian mendalam tentang Kalender Hijriah Unifikatif ini dari sudut pandang fikih, yaitu kajian mengenai penggunaan hisab, pemahaman tentang matlak dan permulaan hari yang keseluruhannya didominasi oleh perbedaan dalam pemahaman terhadap landasan syar’i berupa al-Qur`an dan hadis. Metodenya dengan cara menginventarisir konsep-konsep fikih berkaitan, kemudian melakukan analisis mendalam dan menarik kesimpulan dari hasil analisis tersebut. Hasilnya, penetapan awal bulan dalam hal ibadah haruslah merujuk kepada wahyu ataupun hadis Rasul saw. bahwa konsep Islam dalam memulai bulan baru adalah disebabkan oleh keberadaan hilal. Solusi untuk penyatuan dalam hal ibadah memang mesti diserahakan kepada otoritas masing-masing negara muslim. Adapun terkait dengan non ibadah bisa diterapkan, namun untuk meminimalisir permasalahan, unifikasi kalender ini harus dimulai terlebih dahulu dalam kontes lokal.